A high-density lithium iron phosphate positive electrode material and its preparation method and application

Spherical lithium iron phosphate is prepared by spray drying and sintering, and combined with mechanical fusion and pulse grinding to form a sheet-like material, which solves the problem of low conductivity of lithium iron phosphate and significantly improves its conductivity and filling efficiency. It is suitable for lithium-ion batteries. Extends the battery cycle life.

CN118771344BActive Publication Date: 2024-12-17银贮(阜阳)科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411273084.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-17
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The low conductivity of lithium iron phosphate and low diffusion kinetics of lithium ion have led to insufficient overall performance in lithium-ion batteries, especially in terms of filling efficiency and cycle life.

Method used

Spherical lithium iron phosphate positive electrode material is prepared by spray drying and sintering, and mechanical fusion and pulse grinding are carried out to form a sheet material, which is then mixed and sintered with the spherical material to form a high-density lithium iron phosphate (LFP/C) positive electrode material, improving its Conductivity and filling efficiency.

Benefits of technology

It significantly improves the conductivity and lithium ion diffusion coefficient of lithium iron phosphate, achieves high volume energy density and high Coulomb efficiency, extends the cycle life of lithium-ion batteries, and is suitable for large electric equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118771344B_ABST
    Figure CN118771344B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of lithium battery technology, and specifically to a high-density lithium iron phosphate positive electrode material and a preparation method and application thereof. The specific preparation method comprises the following steps: fully mixing an iron source, a phosphorus source, a lithium source, a carbon source, a dispersant, and a solvent, and obtaining LFP / C microspheres through spray drying and high-temperature sintering. Then, a portion of the LFP / C microspheres are mechanically fused to form flaky LFP / C, and finally, the LFP / C microspheres and the flaky LFP / C are mixed and pressed into shape according to a certain proportion, and then sintered at a high temperature to obtain a high-density LFP / C positive electrode material. The present invention achieves a comprehensive improvement in the compaction density and electrical properties of lithium iron phosphate through a simple method. The preparation method is simple, no additional process equipment is required, the grinding efficiency is good, the production energy consumption is low, and it has a prospect for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a high-density lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) have high gravimetric and volumetric energy density and moderate cost, making them the most widely used batteries in consumer electronics, electric vehicles, and grid storage applications. However, compared with layered oxide cathodes, LFP has a low conductivity and Li + In order to improve the overall performance of LFP, particle size reduction and carbon coating are generally used to reduce Li + The diffusion distance of LFP increases the electronic conductivity. However, reducing the particle size leads to poor material processing performance and enhanced reaction with the electrolyte due to the increase in surface area. In addition, the volumetric capacity is also affected by the size reduction, which leads to poor packing efficiency and low cathode active loading. A major obstacle to achieving greater LFP active loading is its poor packing efficiency.

[0003] CN110429277 discloses a method for preparing a high-density LFP / C positive electrode material with high compaction and high rate performance. Using PVP as a dispersant and graphite as a carbon source to control the morphology in the lithium iron phosphate process, the filling efficiency and charge and discharge rate performance of the lithium iron phosphate positive electrode material are greatly improved. CN116750739 discloses a method for preparing a high-density lithium iron phosphate material, which greatly improves the quality of lithium iron phosphate that can be sintered per unit time, thereby reducing production costs. However, the electrical conductivity of lithium iron phosphate is low, the lithium ion diffusion kinetics is low, and the improvement of electrical conductivity, stability, etc. is still limited. The prior art lacks reliable technology to solve these defects. Summary of the invention

[0004] In view of this, the purpose of the present invention is to propose a high-density lithium iron phosphate positive electrode material and its preparation method and application, so as to solve the problems of low electrical conductivity and low ion diffusion coefficient of lithium iron phosphate; at the same time, the cycle life and high-rate performance of lithium-ion batteries can be improved.

[0005] Based on the above purpose, the present invention provides a method for preparing a high-density lithium iron phosphate positive electrode material, comprising the following steps:

[0006] S1. Add lithium source, iron source, phosphorus source, carbon source and dispersant into water, and prepare spherical lithium iron phosphate positive electrode active material by spray drying and sintering.

[0007] S2, subjecting part of the spherical lithium iron phosphate positive electrode active material obtained in step S1 to mechanical fusion treatment and pulse grinding to form flaky lithium iron phosphate;

[0008] S3, the spherical lithium iron phosphate positive electrode active material in step S1 and the flaky lithium iron phosphate in step S2 are ball-milled, sand-milled, dried, pressed, and sintered to obtain a high-density lithium iron phosphate (LFP / C) positive electrode material. Compared with the traditional LFP / C electrode, the high-density LFP / C electrode prepared by the preparation method of the present invention has higher coulomb efficiency and significantly reduces the charge transfer resistance. The reason is that the densified LFP / C forms a fast lithium ion grain boundary diffusion, achieving high volume energy density and high coulomb efficiency.

[0009] In step S1, the amount of the lithium source, iron source, phosphorus source and carbon source added is in a molar ratio of Li, Fe, P and C of 1.01-1.03: 0.98-1.0: 1: 0.4-0.6; the amount of the dispersant added is 5-10% of the weight of the lithium source.

[0010] In step S1, the lithium source is one or more of lithium hydroxide, lithium carbonate, and lithium oxalate; the iron source is one or more of iron oxide, ferrous oxalate, and ferric chloride; the phosphorus source is one or more of phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; the carbon source is one or more of starch, glucose, lauric acid, acetylene black, sucrose, and graphite; the dispersant is one or more of polyvinyl pyrrolidone, sorbitol, polyethylene glycol, polyvinyl alcohol, sodium dodecyl sulfate, and hexamethylenetetramine.

[0011] During the spray drying in step S1, the air inlet temperature is 180-240° C., and the outlet temperature is controlled at 80-120° C. Preferably, centrifugal spray drying is adopted, the feed rate is 20-60 rpm, and the atomizing disk speed is 15000-20000 rpm.

[0012] The sintering temperature in step S1 is 400-600°C. Here, low-temperature sintering is used to prepare spherical lithium iron phosphate in order to maintain a certain sintering activity. During the high-temperature sintering in step 3, grain growth is promoted and the gaps between particles are reduced to achieve high density requirements.

[0013] When mechanical fusion and pulse grinding are performed in step S2, the template particles used in the mechanical fusion process have a diameter of 50 μm zirconium dioxide balls, a rotation speed of 1200-1500 rpm, a pressure head gap of 1.2-1.4 mm, a scraper gap of 0.5-0.8 mm, and an impact mill performs 15-20 pulse grinding on the template particles. The purpose of mechanical fusion and pulse grinding is to press spherical lithium iron phosphate on the surface of the template particles to form flaky lithium iron phosphate, and finally separate the flaky lithium iron phosphate and the template particles by screening.

[0014] The ball milling speed in step S3 is 200-600r / min, and the time is 1-3h. The sand milling speed is 1000-2000r / min, and the particle size D50 is controlled to be 100-300nm. During the sand milling, the slurry particle size is continuously tested in combination with a laser particle size analyzer. If the sand milling particle size is too large, not only will it lead to an excessively high sintering temperature and an extension of the sintering time, but it will also make the phased lithium iron phosphate grains larger, increase the diffusion path of lithium ions, and lead to low electrical properties. If the particle size is too small, problems such as incomplete crystallinity and poor processing performance will occur.

[0015] The pressure during the pressing process in step S3 is 200-600t and the time is 10-30min. The pressing process can discharge the air between the powders and compress the gaps between the powders. On the other hand, the close contact between the powders is more conducive to mass and heat transfer during the high-temperature sintering process, promoting grain growth, thereby achieving high density requirements.

[0016] The sintering temperature in step S3 is 500-700° C. and the sintering time is 6-12 hours.

[0017] In step S3, the primary particle sizes of the spherical lithium iron phosphate and the flake lithium iron phosphate after ball milling and sand milling are the same, and the flake lithium iron phosphate can be filled between the spherical lithium iron phosphate, which greatly increases the filling efficiency.

[0018] The present invention also provides a high-density lithium iron phosphate positive electrode material obtained by adopting the preparation method.

[0019] The present invention also provides the application of the high-density lithium iron phosphate positive electrode material in power equipment. The lithium iron phosphate positive electrode material with low surface area, low polarization rate, high rate performance and high ion conductivity is obtained by morphology control and modification in the lithium iron phosphate process, which has a profound impact on the application of lithium batteries.

[0020] Beneficial effects of the present invention: The high-density lithium iron phosphate positive electrode material prepared by the present invention forms a rapid lithium ion grain boundary diffusion, achieves high volume energy density and high Coulomb efficiency, significantly reduces the charge transfer resistance, and can thereby improve the conductivity and lithium ion diffusion coefficient of the lithium iron phosphate material, can have high specific capacity and good cycle performance under high current density conditions, and can be suitable for use as a battery positive electrode material for some large electric equipment. The preparation method provided by the present invention greatly reduces the concentration polarization of LFP / C, and the electrode porosity is only 10~14% under high load. Compared with traditional LFP, the resulting flaky particles and microsphere morphology improve the filling efficiency, and its volume energy density is increased by 20~30%. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 A flow chart is prepared for the present invention;

[0023] Figure 2 This is the XRD spectrum of the high-density lithium iron phosphate positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION

[0024] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0025] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should have the common meanings understood by persons having ordinary skills in the field to which the present invention belongs. Embodiment 1

[0026] The preparation method of the high-density lithium iron phosphate positive electrode material of this embodiment is as follows:

[0027] (1) weighing the raw materials required for preparing lithium iron phosphate according to a lithium: iron: phosphorus molar ratio of 1.02:1:1: 740 g of lithium carbonate, 528.8 g of ferrous oxalate, 1150.3 g of ammonium dihydrogen phosphate, 50 g of glucose and 2000 g of deionized water, and stirring them evenly to form a slurry;

[0028] (2) spray drying the slurry obtained in step (1) at an inlet temperature of 220° C. and an outlet temperature of 95° C. to obtain a precursor powder;

[0029] (3) The precursor powder obtained by spray drying is heated to 450° C. at a heating rate of 3° C. / min in an inert atmosphere of nitrogen and kept at this temperature for 5 h to obtain spherical lithium iron phosphate after pre-sintering.

[0030] (4) 200 g of spherical lithium iron phosphate obtained in step (3) is subjected to mechanical fusion treatment and pulse grinding to form a mixture of flaky lithium iron phosphate and template particles, and the flaky lithium iron phosphate is separated from the mixture using a 200-mesh screen. The template particles used in the mechanical fusion process have a diameter of 50 μm zirconium dioxide balls, a rotation speed of 1200 rpm, a pressure head gap of 1.3 mm, a scraper gap of 0.6 mm, and the impact mill performs 16 pulse grindings on the template particles.

[0031] (5) The spherical lithium iron and the flake lithium iron obtained in steps (3) and (4) were ball-milled at a mass ratio of 5:5 at 300 r / min for 1 h to form a uniformly mixed slurry.

[0032] (6) The slurry obtained in step (5) was sand-milled at a rotation speed of 1500 r / min until D50 was 200 nm, and then spray-dried at an inlet temperature of 220° C. and an outlet temperature of 100° C. to obtain a precursor powder.

[0033] (7) The precursor obtained in step (6) is pressed at a pressure of 400t for 15 minutes to obtain a circular embryo body, and finally the pressed embryo body is sintered under nitrogen according to the following steps: the temperature is raised from room temperature to 600°C and kept for 8 hours to obtain a high-density lithium iron phosphate positive electrode material. Embodiment 2

[0034] This embodiment provides a lithium iron phosphate material, and its preparation method is the same as that of Embodiment 1, except that: in step (1), the molar ratio of lithium: iron: phosphorus is 1.01:1:1, and in step (5), the mass ratio of spherical lithium iron phosphate to flake lithium iron phosphate is 6:4. Embodiment 3

[0035] This embodiment provides a lithium iron phosphate positive electrode material, and its preparation method is the same as that of Example 1, except that: in step (1), the molar ratio of lithium: iron: phosphorus is 1.03:1:1, and in step (5), the mass ratio of spherical lithium iron phosphate to flake lithium iron phosphate is 7:3. Embodiment 4

[0036] This embodiment provides a lithium iron phosphate positive electrode material, and its preparation method is the same as that of Embodiment 1, except that in step (5), the mass ratio of spherical lithium iron phosphate to flake lithium iron phosphate is 8:2.

[0037] Comparative Example 1

[0038] The preparation method of the composite material of this comparative example is as follows:

[0039] This comparative example provides a lithium iron phosphate material, and its preparation method is the same as that of Example 1, except that in step (5), the mass ratio of spherical lithium iron phosphate to flake lithium iron phosphate is 4:6.

[0040] Comparative Example 2

[0041] The preparation method of the composite material of this comparative example is as follows:

[0042] This comparative example provides a lithium iron phosphate material, and its preparation method is the same as that of Example 1, except that in step (5), the mass ratio of spherical lithium iron phosphate to flake lithium iron phosphate is 3:7.

[0043] Comparative Example 3

[0044] This comparative example provides a lithium iron phosphate material, and its preparation method is the same as that of Example 1, except that in step (5), the mass ratio of spherical lithium iron phosphate to flake lithium iron phosphate is 2:8.

[0045] Comparative Example 4

[0046] The only difference between this comparative example and Example 1 is that the lithium ion positive electrode materials are all sheet-like lithium iron phosphate materials.

[0047] Comparative Example 5

[0048] The only difference between this comparative example and Example 1 is that all lithium ion positive electrode materials are spherical lithium iron phosphate materials.

[0049] The above examples and comparative examples are used as positive electrode materials for lithium-ion batteries. The positive electrode materials, conductive agents, and binders (PVDF) are made into slurries and evenly coated on aluminum foil, then vacuum dried, compacted by a roller machine, and punched into circular pole pieces. Metal lithium sheets are used as negative electrode materials for lithium-ion batteries, PC is used as a diaphragm, and LiPF6 / (EC+DMC+DEC) (volume ratio 1:1:1) with a concentration of 1 mol / L is used as an electrolyte. Button half-cells are assembled in a vacuum glove box, and constant current charge and discharge and rate performance tests are performed as shown in Table 1 below.

[0050]

[0051] like Figure 2 The figure shows the XRD spectrum of Example 1 of the fully dense lithium iron phosphate positive electrode material prepared by the present invention. As can be seen from the figure, the characteristic peak of the sample shows an olivine structure without other impurities, indicating that the morphology will not change the crystal structure of lithium iron phosphate. In addition, the diffraction peaks of the sample are very sharp and the diffraction intensity is very high, indicating that the sample has good crystallinity.

[0052] Combined with the experimental data in Table 1, it can be seen that the obtained high-density lithium iron phosphate positive electrode material has good cycle life and rate performance. The composite lithium iron phosphate of Example 3 exhibits the highest rate performance and the best cycle performance. The reason is that an appropriate amount of flaky lithium iron phosphate is filled between the spherical lithium iron phosphate to form a densified structure. The densified structure transforms the lithium ion conduction between the particles into grain boundary conduction, which greatly reduces the charge resistance. Compared with Example 4, a small amount of flaky particles cannot fill all the gaps in the spherical lithium iron phosphate, resulting in a high porosity and poor rate performance. For Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, as the proportion of flaky lithium iron phosphate increases, the rate performance is also weakened accordingly. The reason may be that too much flaky lithium iron phosphate forms a disordered accumulation, resulting in a large porosity inside the lithium iron phosphate, which seriously hinders the migration of lithium ions. The spherical lithium iron phosphate of Comparative Example 5 has a higher rate performance than the flaky lithium iron phosphate of Comparative Example 4, indicating that the porosity of the spherical lithium iron phosphate is low. In short, when an appropriate amount of flake lithium iron phosphate is filled between spherical lithium iron phosphate, the conduction of lithium ions can be promoted and its rate performance can be improved.

[0053] Those skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a high-density lithium iron phosphate positive electrode material, characterized in that: The steps include: S1. Adding a lithium source, an iron source, a phosphorus source, a carbon source and a dispersant into water, spray drying and sintering to prepare a spherical lithium iron phosphate positive electrode active material; S2, converting part of the spherical lithium iron phosphate obtained in S1 into flake lithium iron phosphate by mechanical fusion and pulse grinding; S3. Ball-milling, sand-milling, drying, pressing, and sintering the spherical lithium iron phosphate positive electrode active material and the flake lithium iron phosphate at a mass ratio of 5-8:2-5 to obtain a high-density lithium iron phosphate positive electrode material.

2. The method for preparing the high-density lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S1, the amount of the lithium source, iron source, phosphorus source and carbon source added is in a molar ratio of Li, Fe, P and C of 1.01-1.03:0.98-1.0:1:0.4-0.6, and the amount of the dispersant added is 5-10% of the weight of the lithium source.

3. The method for preparing the high-density lithium iron phosphate positive electrode material according to claim 1, characterized in that: The sintering temperature in step S1 is 400-600° C. and the sintering time is 4-8 hours.

4. The method for preparing the high-density lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S1, the lithium source is one or more of lithium hydroxide, lithium carbonate, and lithium oxalate; the iron source is one or more of iron oxide, ferrous oxalate, and ferric chloride; the phosphorus source is one or more of phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; the carbon source is one or more of starch, glucose, lauric acid, acetylene black, sucrose, and graphite; the dispersant is one or more of polyvinyl pyrrolidone, sorbitol, polyethylene glycol, polyvinyl alcohol, sodium dodecyl sulfate, and hexamethylenetetramine.

5. The method for preparing the high-density lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S2, the diameter of the template particles used in the mechanical fusion process is 50 μm zirconium dioxide balls, the rotation speed is 1200-1500 rpm, the pressure head gap is 1.2-1.4 mm, the scraper gap is 0.5-0.8 mm, and the impact mill performs 15-20 pulse grinding on the template particles.

6. The method for preparing the high-density lithium iron phosphate positive electrode material according to claim 1, characterized in that: The ball milling speed in step S3 is 200-600r / min, and the time is 1-3h; the sand milling speed is 1000-2000r / min, and the particle size D50 is controlled to be 100-300nm; the drying in step S3 adopts spray drying, and the air inlet temperature during spray drying is 180-240°C, and the outlet temperature is controlled at 80-120°C.

7. The method for preparing the high-density lithium iron phosphate positive electrode material according to claim 1, characterized in that: The pressure during the pressing process in step S3 is 200-600t and the time is 10-30min. The temperature during the sintering process in step S3 is 500-700°C and the time is 6-12h.

8. A high-density lithium iron phosphate positive electrode material, characterized in that: The preparation method according to any one of claims 1 to 7 is used to obtain the 9. Use of the high-density lithium iron phosphate positive electrode material according to claim 8 in power equipment.